An assocaition between organisational growth and profitability: a study of commercial bank of ceylon ltd srilanka - Velnampy, T.; Nimalathasan, B. (University of Jaffna, 2008)
The banking organizations, today, is moving towards the goal of integrated financial services because of the strong competition and quick changes of technology. In developing countries like Sri Lanka, banking organizations provide fund for other organisatinal developments. Financial system of a country is broadly the mechanism in the financial market which deals with the business or transactions in money .The financial sector in every country has become the deciding factor of the economy. The implementation and achievement of the government policies, let it be developing / developed depends on the financial market. There should be a steady financial policy of the government, further more, financial stability be maintained by the state. Today banking sector plays a significant role in the economic development of the country. The present study is initiated an association between organizational growth and profitability of virtually all of the Banks’ branches of Commercial bank of Ceylon Ltd in SriLanka with last 10 years accounting period: 1997-2006.Correlation analysis shows that, Return on Average Assets (RAA), Return on Average Share holders (RAS) are significantly associated with number of advances and number of depositors and sales are correlated with all profitability ratios except ROE and ROI. Further organizational growth has a greater impact on all profitability ratios.
Keywords: Banking; Organisational growth; Profitability; Advances; Deposit